The effects of domestic sludge and diammonium phosphate on yield and yield components of haricot bean (Phaseolus vulgaris L.) and soil characteristics - Markos Mathewos; Melkamu Dugassa; Kassahun Gashu Melese; Abiot Ketema; Tewodros Assefa Nigussie (Discover Sustainability)
Abstract A pot experiment was carried out in a shade house at Hawassa University in 2023 to evaluate the effects of rates of domestic sludge (0, 10, and 20 t/ha) in combination with three levels of diammonium phosphate (0, 50 and 100 kg/ha). The treatments were executed in a pot with soil capacity of 6 kg having 9 treatments each replicated three times and arranged in a completely randomized design. The results showed that yield and yield related parameters of Haricot bean showed a positive response to domestic sludge, diammonium phosphate fertilizer rates and their interactions. The interaction effects significantly affected days to flowering and days to maturity. The interaction of domestic sludge and diammonium phosphate significantly affected the entire yield and yield related parameters assessed in this study. The maximum number of pods per plant (19) was recorded from the application of 20 t/ha domestic sludge + 0 kg diammonium phosphate with statistically similar result to most the treatments while the minimum was recorded from the control. Compared to the control, application of 20 t/ha domestic sludge + 0 kg diammonium phosphate increased the number of pods per plant by 21.25%. The maximum (28.24 g) grain yield per plant was obtained from application of 10 t/ha domestic sludge + 100 kg diammonium phosphate while the lowest (15.99 g) was obtained from the control. As compared to the control, the application of 10 t/ha domestic sludge + 100 kg diammonium phosphate increased the grain yield by 76.61%. In conclusion, based on the results of the current study, domestic sludge could be considered for use either alone or in combination with diammonium phosphate fertilizer in haricot bean production to increase the productivity of the crop. Application of 10 t/ha domestic sludge + 100 kg diammonium phosphate surpassed the other combination of treatments and therefore could be recommended as the best combination for use. The domestic sludge application caused significant changes in soil macro-element content especially phosphorus, organic carbon, and total nitrogen, improved soil physical and chemical contents of the soil. In addition, domestic sludge can be used as an alternative to chemical fertilizers whose costs are escalating beyond the purchasing powers of the crop producers of smallholders.